Land management objectives and activities in the face of projected fire regime change in the Sonoran desert. (15th February 2021) - Aslan, Clare E.; Souther, Sara; Stortz, Sasha; Sample, Martha; Sandor, Manette; Levine, Carrie; Samberg, Leah; Gray, Miranda; Dickson, Brett
Abstract: As a multi-jurisdictional, non-fire-adapted region, the Sonoran Desert Ecoregion is a complex, social-ecological system faced increasingly with no-analogue conditions. A diversity of management objectives and activities form the socioecological landscape of fire management. Different managers have different objectives, resources, and constraints, and each therefore applies different activities. As a result, it can be difficult to predict the regional consequences of changing fire regimes. We interviewed and surveyed managers of 53 million acres of government-managed lands across the Sonoran Desert Ecoregion of Arizona, asking them to describe their management objectives and activities as well as expected changes in the face of projected fire regime change across the region. If current activities were deemed unlikely to meet objectives into the future, this represents a likely adaptation turning point, where new activities are required in order to meet objectives. If no potential activity will meet an objective, it may be necessary to select a new objective, indicating an adaptation tipping point. Here, we report which current objectives and activities are deemed by managers most likely and least likely to succeed. We also discuss constraints reported by managers from different jurisdictions. We find that agriculture, military, and resource extraction objectives are perceived by managers as most likely to be met, whereas conservation of natural and cultural resources is considered least likely to be achieved. Federal land managers reported higher likelihood of both achieving current objectives and adopting new activities than did non-federal land managers. This study illustrates how rapid global change is affecting the ability of land managers differing in missions, mandates, and resources to achieve their central objectives, as well as the constraints and opportunities they face. Our results indicate that changing environmental conditions are unlikely to affect all management entities equally and for some jurisdictions may result in adaptation turning points or tipping points in natural and cultural resource conservation. Highlights: Environmental change can drive social-ecological states toward tipping points In interviews, land managers described adaptation in response to fire regime change Fire regime change will likely obstruct cultural resource and recreation objectives Military and economic objectives are least affected by shifts in fire regimes New social-ecological states are likely when management objectives shift